2004
DOI: 10.1097/01.inf.0000143647.88873.66
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Bacterial Infection in Previously Healthy Respiratory Syncytial Virus-Infected Young Children Admitted to the Intensive Care Unit

Abstract: Objective-To evaluate the risk of bacterial infection and use of antibiotics in otherwise healthy children infected with respiratory syncytial virus (RSV) admitted to the intensive care unit (ICU).Methods-Demographics, clinical information, interventions and outcomes were extracted from the charts of consecutive patients with laboratory-confirmed RSV infection at Children's Hospital, Boston from October 1990 through April 2002. Patients born at <36 weeks gestational age or with preexisting medical conditions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
2
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 12 publications
(11 reference statements)
6
83
2
1
Order By: Relevance
“…4). In a series of studies examining patients admitted to hospitals with RSV infections, between 17.5 and 44% of patients also tested positive for a lower respiratory tract bacterial coinfection, with Streptococcus pneumoniae (Gram positive) and Haemophilus influenzae (Gram negative) being the most common bacterial isolates (191)(192)(193)(194)(195). Compared to RSV infection alone, a bacterial coinfection combined with RSV infection correlates with more severe disease (64,191,192,194).…”
Section: Rsv and Bacterial Colonizationmentioning
confidence: 99%
“…4). In a series of studies examining patients admitted to hospitals with RSV infections, between 17.5 and 44% of patients also tested positive for a lower respiratory tract bacterial coinfection, with Streptococcus pneumoniae (Gram positive) and Haemophilus influenzae (Gram negative) being the most common bacterial isolates (191)(192)(193)(194)(195). Compared to RSV infection alone, a bacterial coinfection combined with RSV infection correlates with more severe disease (64,191,192,194).…”
Section: Rsv and Bacterial Colonizationmentioning
confidence: 99%
“…Analysis of influenza pandemics showed that the incidence of bacterial pneumonia was increased and contributed substantially to mortality rates (Abrahams et al, 1919;Muir & Wilson, 1919;Stone & Swift, 1919;Wilson & Steer, 1919). Comparison of bacteriological and virological data from children hospitalized for respiratory disease shows a high degree of occurrence of viral and bacterial infections positively correlating with the severity of illness (Duttweiler et al, 2004;Kneyber et al, 2005;Randolph et al, 2004;Thorburn et al, 2006). Although the role of a preceding viral infection in development and severity of bacterial respiratory diseases is a clinically welldocumented phenomenon, the exact mechanism has not been elucidated fully.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in calves raised on farms, RSV-induced lung disease is characterized by intense neutrophilic inflammation, mucopurulent exudate, and growth of a variety of bacterial pathogens, suggesting the presence of bacterial superinfection (2,35). Such secondary infection is extremely uncommon in human infants with RSV infection (28). When calves are raised in germ-free environments, bovine RSV challenge can result in pneumonia, but the disease seems to be lymphocyte-mediated, as it is in rodents (1).…”
mentioning
confidence: 99%